Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Simulasi Pada Materi Mitigasi Bencana Alam - Syahril Lukman; Dahri Hi Halek; Siti Basaria Damra (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the increase in student learning outcomes through a simulation learning model on natural disaster mitigation material. The subject of this research was class XI SMA Muhammadiyah Ternate, which consisted of 20 students. The type of research used is Classroom Action Research (CAR) or Classroom Action Research, with research procedures starting from the planning, action, observation, and reflection stages. This research consisted of 2 cycles, namely cycle I and cycle II. Learning using this simulation learning model is carried out with the syntax of orientation, participation training, simulation implementation, participant interviews. The results of the study show that the simulation learning model can improve student learning outcomes in natural disaster mitigation material. This can be seen from the percentage of students who have reached the KKM. In the pre-cycle the percentage of classical completeness only reached 55% or 11 students out of 20 students who had reached KKM, in cycle I the percentage of classical completeness increased by 75% or 15 students out of 20 students who had reached KKM, and in cycle II the percentage of classical completeness to 90% or 18 students out of 20 students who have achieved KKM.